Konsep Independent Regulatory Agencies Dalam Kewenangan DKPP Sebagai Lembaga Peradilan Etik - Muchlisin (As-Shahifah : Journal of Constitutional Law and Governance, 2021)
The research in this journal discusses the authority of the Election Organizing Honorary Council (DKPP). DKPP is one of the triumvirate election organizers in Indonesia whose authority is to handle problems that occur between Election Organizing Institutions. This research uses normative law research methods by using several approaches including statute approach, case approach, and conceptual approach. In the Political Law of Elections in Indonesia, the status a quo gives the DKPP such coercive authority related to the enforcement of the code of ethics. However, over time, there is a problem that considers that DKPP has exceeded the limits of its authority as an Ethics Institute. Moreover, after the transfer of his secretariat to the Ministry of Home Affairs, it was feared that it would interfere with the independence of the DKPP as one element of the election organizers. Because basically the EMB must be independent and with integrity. The transfer is based on Presidential Decree No. 67 of 2018. This should not have happened because the Elections Organizing Body does not only handle the legislative election process but also the Executive. So it is feared when this happens it will interfere with the independence of the DKPP. Bearing in mind that, the decision of the DKPP is final and binding.